Almond-like aroma formation of acid whey by ischnoderma benzoinum fermentation: potential a in novel beverage development - Hannemann, Lea; Klauss, Raphaela; Gleissle, Anne; Heinrich, Patrick; Braunbeck, Thomas; Zhang, Yanyan (Journal of agricultural and food chemistry, 2025)
To address the sourish off-aroma of acid whey and enhance its upcycling, a new basidiomycete Ischnoderma benzoinum-mediated fermentation system was developed using pure acid whey as the sole substrate. A pleasant sweetish and marzipan-like odor was perceived after fermentation within 7 d at 24 °C in darkness, which was shaped from key contributors including 4-methoxybenzaldehyde (odor activity value (OAV) 878), 3-methylbutanal (OAV 511), 3,4-dimethoxybenzaldehyde (OAV 50), and benzaldehyde (OAV 28). The typical sweetish and almond-like odor persisted well after ultrahigh-temperature processing, though its intensity decreased slightly. Concurrently, the fermentation reduced lactose from 52 to 20 g/L but increased the contents of essential amino acids like threonine, leucine, and lysine. No significant cytotoxicity or genotoxicity differences were found between fermented and unfermented whey. Overall, the study highlights the capability of I. benzoinum fermentation to enhance the flavor of acid whey, offering a promising approach for creating nutritional and flavorful acid-whey-based products.
Gesehen am 09.09.2025